2005
DOI: 10.1002/art.21035
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of radiographic and clinical variables to pinch and grip strength among individuals with osteoarthritis

Abstract: Objective. Little is known about how specific radiographic features are related to hand strength in osteoarthritis (OA). This study examined associations of radiographic variables with pinch and grip strength among individuals with radiographic hand OA.Methods. Participants (n ‫؍‬ 700, 80% female, mean age 69 years) were part of a study on the genetics of generalized OA. All had bilateral radiographic hand OA. Linear models were used to examine associations of grip and pinch strength with 1) OA in joint groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 19 publications
3
75
1
3
Order By: Relevance
“…Involvement of MCP joints in OA without node formation is less apparent but is evidenced with different methods (21). JSW of MCP and PIP joints is normal in early RA (18), but is reduced in the case of coexisting OA (22).…”
Section: Discussionmentioning
confidence: 98%
“…Involvement of MCP joints in OA without node formation is less apparent but is evidenced with different methods (21). JSW of MCP and PIP joints is normal in early RA (18), but is reduced in the case of coexisting OA (22).…”
Section: Discussionmentioning
confidence: 98%
“…Many authors have studied the effect of OA on hand function and have had contradictory results [3,5,7,14,20,27]. Baron et al [3] reported no correlation between hand strength and the degree of radiologic hand OA.…”
Section: Discussionmentioning
confidence: 99%
“…If at least one joint of that digit-joint group had radiographic OA, that group had OA. To quantify the overall radiographic severity of hand OA in each digit-joint group, we summed the Kellgren and Lawrence grades of three joints (DIP, PIP, MCP) in each of the four fingers, and of the IP, MCP, and CMC joints in the thumb [5].…”
Section: Methodsmentioning
confidence: 99%
“…Studies support an association of advanced age, female sex, family history, and increased BMI with CMC OA [2,6,16,30]. Pinching tasks are especially uncomfortable for patients with early OA, and patients with CMC and distal interphalangeal arthritis have been shown to have lower pinch and grip strength [1,5,8,17,24]. The extent to which this weakness during functional tasks informs the diagnosis of early CMC OA has been preliminary but not rigorously quantified in the literature [15,22].…”
Section: Introductionmentioning
confidence: 99%